2015
DOI: 10.1007/s00405-015-3501-4
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of thermocoagulative injury via use of a picosecond infrared laser (PIRL) in laryngeal tissues

Abstract: The carbon dioxide (CO2) laser is routinely used in glottic microsurgery for the treatment of benign and malignant disease, despite significant collateral thermal damage secondary to photothermal vaporization without thermal confinement. Subsequent tissue response to thermal injury involves excess collagen deposition resulting in scarring and functional impairment. To minimize collateral thermal injury, short-pulse laser systems such as the microsecond pulsed erbium:yttrium-aluminium-garnet (Er:YAG) laser and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Ex vivo soft tissue incisions made with PIRL have demonstrated nearly complete absence of thermal injury and much narrower cutting gaps when compared to CO 2 laser and scalpel . Infrared thermography has shown minimal ex vivo skin, mucosa, bone, and cartilage temperature rise during ablation using PIRL in contrast to Er:YAG‐Laser . Further, the detection of protein activity and intact higher order protein structure in the ablation‐aerosol emphasizes the soft character of the DIVE‐ablation process .…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo soft tissue incisions made with PIRL have demonstrated nearly complete absence of thermal injury and much narrower cutting gaps when compared to CO 2 laser and scalpel . Infrared thermography has shown minimal ex vivo skin, mucosa, bone, and cartilage temperature rise during ablation using PIRL in contrast to Er:YAG‐Laser . Further, the detection of protein activity and intact higher order protein structure in the ablation‐aerosol emphasizes the soft character of the DIVE‐ablation process .…”
Section: Discussionmentioning
confidence: 99%
“…The soft ablation of tissue by PIRL is achieved under the conditions of desorption by impulsive excitation (DIVE) [21] in which the water molecules contained within the tissue are transferred into the gas phase in an ultrafast, explosive manner. DIVE results in intact cellular biomolecules blasting out of the sample with minimized heating or shock wave damage imposed on the tissue and biomolecules [22] , [23] , [24] , [25] . Kwiatkowski et al showed that the tissue proteome is present in the condensate of the DIVE-induced tissue aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…The energy absorbed by the tissue-own water molecules is completely converted into translational degrees of freedom rather than being lost to surrounding tissue through thermal or acoustic transport. This process called ‘desorption by impulsive vibrational excitation’ [96] drives the water molecules into the gas phase without thermal or shock-wave damage to the ambient tissue, resulting in cold tissue vaporization [97]. The unique properties of PIRL enable precise and accurate ablation with minimal cellular damages to the surrounding tissue, significantly reducing scar formation compared with millisecond infrared lasers commonly used in medical laser surgery [97–104].…”
Section: Ms-based Methods For Intraoperative Tumor Diagnosticsmentioning
confidence: 99%
“…This process called ‘desorption by impulsive vibrational excitation’ [96] drives the water molecules into the gas phase without thermal or shock-wave damage to the ambient tissue, resulting in cold tissue vaporization [97]. The unique properties of PIRL enable precise and accurate ablation with minimal cellular damages to the surrounding tissue, significantly reducing scar formation compared with millisecond infrared lasers commonly used in medical laser surgery [97–104]. Next to the medical application, the group of Hartmut Schlüter showed that PIRL ablation released proteins intact from tissues without changing their exact chemical composition and that posttranslational modifications and enzyme activities of the PIRL-ablated proteins remained unaltered [96].…”
Section: Ms-based Methods For Intraoperative Tumor Diagnosticsmentioning
confidence: 99%